Value relevance of voluntary intellectual capital disclosure: a meta-analysis - Robert Rieg; Ute Vanini (Review of Managerial Science, 2023)
Because mandatory disclosure of intellectual capital (IC) is restricted by accounting regulations, companies invest in voluntary IC disclosure (ICD) to reduce information asymmetries and support an adequate firm valuation by investors and other stakeholders. So far numerous studies analysing the value relevance of voluntary ICD have been published revealing mixed results. Thus, it is the purpose of this paper to statistically integrate and to explain the heterogeneity of results by applying a meta-analysis with 122 effects of 40 primary studies. Our results mainly support the value relevance of voluntary ICD resulting in higher market value, lower cost of equity, and higher accounting performance. We identify weak moderating effects for legal origin, different IC categories and journal ranking. For further improving of disclosure quality, standard setters should develop disclosure standards for voluntary ICD. To reduce the heterogeneity of future studies a standardised scale for the measurement of voluntary ICD should be developed and applied.
Keywords: M10; M41; 650; Intellectual capital; Voluntary disclosure; Meta-analysis; Financial effects; Moderating variables; Value relevance